BUILD STOCK PORTFOLIO USING COMBINATION OF MINERVINI STOCK SCREENER TEMPLATE AND MARKOWITZ PORTFOLIO OPTIMIZATION METHOD - Syaifudin, Fahmi
The main problem that investors face when investing in the stock market is (1) which stocks to buy? (2) When should I buy a stock? (3) When should I sell a stock? (4) How many shares should I buy? Answering four important questions that will inevitably arise as new investors enter the capital market will require a comprehensive of analyses. Fundamental analysis often reveals only which stocks are worth buying. While technical analysis is commonly used to determine when to sell or buy stocks. The study will use both technical and fundamental analysis. Implemented the Minervini Trend Template strategy, the Simple Moving Average (SMA) indicator is used to distinguish up trending stocks from other stocks. Using simple financial ratios like Market Capitalization, Return on Equity, Price to Earnings, and Price to Book Value, these ratios employed to ranks the filtered stocks. Between 2017 and 2020, the series of the data is back tested its Holding Period Return using SMA Strategy, one year, two years, and three years holding period. The study's final stage involves building a filtered stock portfolio using Markowitz theory. The strategy's back test results show that the constructed portfolio has a decent holding period return. The highest average return is 213,84% for a stock portfolio ranked by Price to Book Value Ratio. The active strategy using Simple Moving Average for stocks selling gave the highest average return of 158,21%. Using the Markowitz method to optimize stock portfolio allocation has shown to benefit investors by reducing risk of volatility.